University selectivity: does it correlate with graduates' wages? Evidence from Chile. (13th January 2022) - Espinoza, Oscar; Sandoval, Luis; González, Luis Eduardo; McGinn, Noel
This paper explores the relationship between university selectivity and graduates' wages. Holding other factors constant, do employers award higher salaries to graduates of universities that impose higher admission requirements? The study looks at wage returns to Chilean graduates in two different disciplines in three universities. The participants were 587 graduates. The results reveal a positive relationship between these factors at high and low selectivity, but not in the middle range. There is no concrete evidence that training in the higher selectivity university is of higher quality. The results advance our understanding of how higher education can contribute to income inequality, but are generalisable only to the two disciplines studied.